Temperature and electrical poling effects on ionic motion in MAPbI3 photovoltaic cells - Bruno, Annalisa (2020)
Despite their excellent power conversion efficiency, MAPbI3 solar cells exhibit strong hysteresis that hinders reliable device operation. Herein it is shown that ionic motion is the dominant mechanism underlying hysteresis of MAPbI3 solar cells by studying the effects of electrical poling in different temperature ranges. Complete suppression of the hysteresis below 170 K is consistent with temperature activated diffusion of I− anions and/or the motion of the MA+ cations. Ionic motion has important effect on the overall efficiency of the MAPbI3 solar cells: the initial decrease of the power conversion efficiency while lowering the operating temperature is recovered and even enhanced up to 20% of its original value by applying an electrical poling. The open circuit voltage significantly increases and the current density fully recovers due to the reduction of the electron extraction barrier at the TiO2/MAPbI3 interface driven by the charge accumulation at the interface. Moreover, beside TiO2/MAPbI3 interfacial charge transfer, charge transport in TiO2 strongly affects the photovoltaic performance, as revealed by MAPbI3/ms‐TiO2 field effect transistors. These results establish the basis to develop effective strategies to mitigate operational instability of perovskites solar cells.